2012
DOI: 10.1002/pssr.201206369
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post‐growth thermal annealing on the emission spectra of GaAs/AlGaAs quantum dots grown by droplet epitaxy

Abstract: We fabricated GaAs/AlGaAs quantum dots by droplet epitaxy, and obtained the geometries of the dots by scanning transmission electron microscopy. Post‐growth thermal annealing is essential for the optical activation of quantum dots grown by droplet epitaxy. We measured the emission energy shifts of the dots and the underlying superlattice by post‐ growth thermal annealing, and specified the emission from dots by selectively etching the structure down to a low layer of quantum dots. We studied the influence of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…From atomic force microscopy (AFM) we found that the uncapped dots were lens-shaped and asymmetric in-plane with a major diameter of (82.4 ± 7.6) nm, a minor diameter of (54.4 ± 12.8) nm and a height of (25.2 ± 8.8) nm but intermixing during overgrowth might change their size. 32 In fact, we will show in sections IV and VI that ground-state excitons are strongly confined, which represents direct evidence of significant interdiffusion during annealing.…”
Section: Sample Growth and Experimental Proceduresmentioning
confidence: 81%
“…From atomic force microscopy (AFM) we found that the uncapped dots were lens-shaped and asymmetric in-plane with a major diameter of (82.4 ± 7.6) nm, a minor diameter of (54.4 ± 12.8) nm and a height of (25.2 ± 8.8) nm but intermixing during overgrowth might change their size. 32 In fact, we will show in sections IV and VI that ground-state excitons are strongly confined, which represents direct evidence of significant interdiffusion during annealing.…”
Section: Sample Growth and Experimental Proceduresmentioning
confidence: 81%
“…Here, the authors should point out that the shape of the GaAs DE QDs is not identical when they are grown on the surface and buried in the AlGaAs matrix. In the case of GaAs DE QDs of reference [ 7 ], the size of GaAs DE QDs on the surface was approximately 12-nm height and approximately 60-nm width and found that approximately 9-nm height and approximately 35-nm width when they were placed in the AlGaAs matrix. Furthermore, the effective size of GaAs DE is additionally reduced due to post-thermal annealing/intermixing and finally gives us the low-temperature PL peaks around 1.70 ~ 1.80 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Less than 10 QDs per μm 2 are preferred for a single photon source application, since optical interference from neighboring QDs could be avoided. Recent results of the growth of low-density QDs have shown that the size, density, and optical quality of QDs are sufficiently controllable [ 3 - 7 ]. In spite of advanced research on the application of low-density QDs, however, these QDs have been exploited in the scale of fundamental research.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the multiple interfaces could be formed during low temperature growth of AlGaAs barrier and thermal annealing process due to the unintentional doping and the additional Al intermixing in GaAs interface during . The introducing of Al atoms into the GaAs can increasing the transition energy of PR spectra.…”
Section: Resultsmentioning
confidence: 99%